Anthracene functionalized thermosensitive and UV-crosslinkable polymeric micelles1. Issue 11 (21st March 2015) - Shi, Yang; Cardoso, Renata M.; van Nostrum, Cornelus F.; Hennink, Wim E.
<x xml:space="preserve">Abstract</x> An anthracene-functionalized thermosensitive block copolymer was synthesized, which formed micelles by heating its aqueous solution above the lower critical solution temperature (LCST). The micelles were subsequently crosslinked by UV illumination at 365 nm with a normal handheld UV lamp.